Role of Lysine Methyl Transferase to p53 Dependent Apoptosis upon Myocardial Infarction - Rehman, Raza; Afzal, Muhammad Asyab; Rehman, Zainab; Ashraf, Shiv Ram; Batool, Saima; Zia, Kashif (Indus Journal of Bioscience Research, 2025)
The reversible protein methylation at lysine residues produces enhancements that boost the signal output of modified factors. The tumor suppressor and transcription factor p53, together with histones, show modified lysine residues through methylation, reflecting this modification acts as one common element for managing essential protein-protein connections and various vital signaling pathways. The research investigates lysine methylation modifications within the terminal region of p53 protein as well as their effects on functional activities. The enzymes which conduct protein post-translational modifications (PTMs) establish an essential regulatory pathway that controls cell processes inside organisms. Every cellular mechanism operates through this post-translational regulatory network as it is responsible for managing each cellular process. Cellular organisms reach biological maturity when different tissues exist in equilibrium while controlling the mechanisms of stem cell development along with cell specialization. Genetic-level cellular state regulation strongly depends on special histone post-translational modifications through lysine methylation processes. Protein substrates receive methyl groups from S-adenosyl-L-methionine through the enzymatic activity of lysine methyltransferases that perform lysine methylation.